The inhibitory effect of the water extract of Olea auvopea on the growth of the ovaries and the digestive tract of the domestic fly Musca domestica L. - Najim Gorgees; Olfat Yaseen; Safaa Mahmoud (College of Education for Pure Sciences, 2009)
Abstract The effect of aqueous extract of Olea auvopea L. on inhibition of ovary growth in house fly Musca domestica L. as well as itُs effect on mid gut tissue structure, at concentrations, 0.5 , 1 , 2.5 and 5 % . Results show significant inhibition of ovary growth and itُs follicles at 1 , 2.5 and 5 % during 24 , 48 hours after emergence. After 72 hours of emergence, the concentrations 0.5 and 5 % were caused significant inhibition in ovary growth and its follicles also these concentrations led to reduction in ovary size and number of follicles as well as lyses with deformity in their shape and sheath. The histological pictures showed separation of circular and longitudinal muscles from basal membrane and undistinguished of epithelial cells and reduction in circular muscles thickness.